2021
DOI: 10.1177/23326492211034890
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Empty Backpack: The Role of Timing in Disproportionate Special Education Identification

Abstract: Studies related to disproportionate special education identification of students from historically marginalized groups have used increasingly complex analyses to understand the interplay of factors that cause and maintain disparities. However, information regarding the influence of students’ grade level at initial special education placement remains limited. Situated in labeling theory and life course theory, we used discrete-time survival analysis to examine temporal student- and school-level factors related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…Most notably, the likelihood of SLD placement for ELs remained lower than that of never-ELs between kindergarten and third grade, but soon outpaced never-ELs’ likelihood for SLD placement at fourth grade and remained elevated into middle school (Umansky et al, 2017). Likewise, studies on SLD representation of Hispanic students—which is the predominant background of ELs in our study—also reported a gradual increase in SLD placement likelihood from lower to upper elementary grades, at which point the likelihood declines (e.g., fifth grade; Morgan et al, 2015) or remains elevated through middle school (Cruz & Firestone, 2022).…”
Section: Discussionsupporting
confidence: 79%
“…Most notably, the likelihood of SLD placement for ELs remained lower than that of never-ELs between kindergarten and third grade, but soon outpaced never-ELs’ likelihood for SLD placement at fourth grade and remained elevated into middle school (Umansky et al, 2017). Likewise, studies on SLD representation of Hispanic students—which is the predominant background of ELs in our study—also reported a gradual increase in SLD placement likelihood from lower to upper elementary grades, at which point the likelihood declines (e.g., fifth grade; Morgan et al, 2015) or remains elevated through middle school (Cruz & Firestone, 2022).…”
Section: Discussionsupporting
confidence: 79%
“…The ways in which BIPOC are pathologized, labeled, and suspended all serve as sources of discrimination that maintain White, ableist power hierarchies. Past research has suggested that although stakeholders have agency in these educational systems, teachers’ perceptions of students also depend on structural factors (Cruz & Firestone, 2021; Fish, 2019; Hibel et al, 2010). Though these factors may be enacted differently in exclusionary discipline than in special education placement, our results provide evidence that students are affected by how practitioners view them within their school contexts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fish (2019) found that school racial composition was linked to the likelihood that African American students would be sorted into more subjective and stigmatizing disability categories. Relatedly, Cruz and Firestone (2021) found that African American and Latinx students were more likely to be diagnosed with subjective disabilities later in their school careers and suggested that teachers pathologized students differently based on perceived preparedness for school—a perception that was often linked to students’ race. This aligned with Okonofua and Eberhardt (2015) finding that students’ race affected how teachers perceived and interpreted behavior, ultimately recommending harsher punishments for African American children even when the behavioral violation was similar and especially after multiple offenses.…”
Section: Interrogating Special Education and Discipline Disparities T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Disability Studies, like other forms of critical inquiry, centers disability as a socially constructed phenomenon, rather than viewing it as a fixed and natural state (see Cruz et al, 2023; Goodley, 2013). Furthermore, Disability Studies challenges researchers to shift the focus from disability at the individual level to view how systems sort, label, disable, and disenfranchise communities (Connor, 2019; Cruz & Firestone, 2021; Reid & Knight, 2006; Skrtic et al, 2021). From this framework, decisions about paraprofessionals should be viewed from a lens of how to best support the environment in which the child learns rather than creating further physical and social isolation from peers (Giangreco, 2021).…”
Section: A Disability Studies Framingmentioning
confidence: 99%